An Assessment of Phytosociological Diversity of Kuther Watershed, Himachal Pradesh, India - Gupta, Peeyush; Uniyal, Swati; Goyal, Swati (International Journal of Environment, 2014)
A plant community acquires many characteristics which are not found in its constituents, (organisms or population). A community is described through species diversity, life forms, structure, dominance and developmental status. To delineate these aspects two significant parameters like analytical characters (quantitative - frequency, density, abundance and cover; qualitative - physiognomy, phenology, sociability, vitality and life form) and synthetic characters (constancy, fidelity and dominance) were studied. The present study focuses on species composition, phytosociological diversity and concentration of dominance of various tree species of Kuther watershed of Himachal Pradesh, India. DOI: http://dx.doi.org/10.3126/ije.v3i4.11732 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 74-90